(untitled) (Nepal Journal of Environmental Science, 2013)
Phewa and Begnas lakes in Pokhara Valley are playing important roles in ecological, economic, cultural and aesthetic aspects. However, due to increase in anthropogenic pressure and activities in the lake catchment, the nutrient load in the lakes has been substantially increased. The growth of algae and phytoplankton is largely dictated by carbon (C), nitrogen (N), phosphorus (P), and silica (Si) availability. Moreover, the increase in P and N loading leads to greater diatom production resulting in the accumulation of biogenic silica (BSi) in sediments. Thus, variation in C, N and BSi in sediment reflects the nutrient dynamics in the lake. In this connection, C, N and Si concentration serves as an indicator for growth of algae, including diatom, phytoplankton productivity, and overall phytoplankton efficiency. The preceding researches have mostly explained limnological characteristics and plankton diversity studies. Hence, information about sediment characteristics associated with nutrient loading and eutrophication seems yet to be wanting. The present study has been carried out to evaluate vertical variation of C, N and BSi in core sediments of the Phewa and Begnas lakes. The C and N was determined by CHNS analyzer and BSi was extracted by wet-alkaline digestion method and determined by molybdosilicate method. The result revealed increase in C, N and BSi contents toward the surface sediments compared to underlying layers suggesting increased rate of accumulation in recent deposits. The magnitude of C, N and BSi was higher in city-ward core of Phewa Lake explaining the influence of the urban inputs ...